Offshore cyber risk in the Marine Industry: limitations and challenges faced by the insurers and policyholders - Seboko, Goitsemang (Department of Commercial Law, 2026)
As stated by Stephen Harris, a mere 30 years ago, the idea of commercial cyber-attack was rather a topic for the science fiction novelists than reality.'1 However, nowadays we witness a growing tendency of reoccurrence of this phenomenon across many sectors that rely on progressively advancing technology. Despite always being known as a conservative field, the maritime industry is no exception in terms of the exposure to risks that result from cyber-attacks.